Homostachydrine (pipecolic acid betaine) as authentication marker of roasted blends of Coffea arabica and Coffea canephora (Robusta) beans. (15th August 2016) - Servillo, Luigi; Giovane, Alfonso; Casale, Rosario; Cautela, Domenico; D'Onofrio, Nunzia; Balestrieri, Maria Luisa; Castaldo, Domenico
Highlights: N -methylpipecolic acid was detected for the first time in coffee beans. Homostachydrine was detected for the first time in coffee beans. Homostachydrine is much more abundant in Robusta than in Arabica seeds. Homostachydrine content is unaffected by coffee bean roasting treatment. The results give a tool to quantify Robusta and Arabica composition of coffee blends. Abstract: The occurrence of pipecolic acid betaine (homostachydrine) and its biosynthetic precursor N- methylpipecolic acid was detected for the first time in green coffee beans of Robusta and Arabica species. The analyses were conducted by HPLC–ESI tandem mass spectrometry and the metabolites identified by product ion spectra and comparison with authentic standards. N- methylpipecolic acid was found at similar levels in green coffee beans of Robusta and Arabica, whereas a noticeable difference of homostachydrine content was observed between the two green coffee bean species. Interestingly, homostachydrine content was found to be unaffected by coffee bean roasting treatment because of a noticeable heat stability, a feature that makes this compound a candidate marker to determine the content of Robusta and Arabica species in roasted coffee blends. To this end, a number of certified pure Arabica and Robusta green beans were analyzed for their homostachydrine content. Results showed that homostachydrine content was 1.5 ± 0.5 mg/kg in Arabica beans and 31.0 ± 10.0 mg/kg in Robusta beans. Finally, to further support the suitability of homostachydrine as quality marker of roasted blends of Arabica and Robusta coffee beans, commercial samples of roasted ground coffee blends were analyzed and the correspondence between the derived percentages of Arabica and Robusta beans with those declared on packages by manufacturers was verified.